KERENTANAN EKOLOGI DAN STRATEGI PENGHIDUPAN PERTANIAN MASYARAKAT DESA PERSAWAHAN TADAH HUJAN DI PANTURA INDRAMAYU - Ali Yansyah Abdurrahim; Arya Hadi Dharmawan; Satyawan Sunito; I Made Sudiana (Research Centre for Population, Indonesian Institute of Sciences, 2014)
Rain fed paddy village in Indramayu North Coasthasa very high ecological vulnerability. Location at the end of the irrigation and flood discharge channel makes this village every year drought in the dry season and floods in the rainy season. Later, the frequency and intensity increase as climate change. This condition is the pressure that shook the liveli hoods of rural communities. To maintain and continue their livelihood, households from various social strata living doing various activities that are grouped into three livelihood strategies, namely (1) agriculture, (2) non-agricultural livelihood diversification, and (3) migration. Livelihood strategies carried out by combining its livelihood assets and livelihood assets belonging to other households who successfully accessible through existing social institutions in rural communities. With a wide range of social institutions that, in general, every household in the village Karangmulya trying to generate sustainable livelihood out comes for the household. Income, well-being (welfare), adaptation of livelihoods, food security, and sustainability of natural resources resulting in a comprehensive and coKeywords: vulnerability, floods, droughts, livelihood strategies, sustainable livelihoods